Evaluation of earth system models outputs over the continental Portuguese coast: a historical comparison between CMIP5 and CMIP6 - Pereira, Humberto (2023)
In the last decades, climate change has been accelerating, affecting, directly and indirectly, the environment, animal habitats, and daily human life. Earth System Models (ESMs) are valuable tools for studying these impacts, and their performance over coastal regions is critical for understanding how physical and biogeochemical processes are evolving through time and how they may change in the future. The continental Portuguese coast, characterized by an important upwelling system, hosts highly productive and nutrient-rich regions with a large diversity of transitional habitats and systems. Therefore, this study aims to evaluate and score the ESMs from the 5th and 6th phases of the Coupled Model Intercomparison Project that better reproduce, simultaneously, physical and biogeochemical ocean properties along the continental Portuguese coast. The analysis was carried out through the computation of a score (SR) between CMIP historical outputs and data from the Iberian-Biscay-Ireland ocean reanalysis system at four selected locations along the coast, considering two physical and four biochemical variables. Results reveal that ESMs perform better for the physical properties than for the biochemical ones, as well as lower differences and variance between CMIP6 models, reflecting an improvement from CMIP5. The Max Planck Institute (MPI) models obtained the best overall classification by delivering a consistently good performance for all variables.